Postmortem evidence of disseminated Zika virus infection in an adult patient - Rajahram, Giri Shan; Hale, Gillian; Bhatnagar, Julu; Hiu, Jessie; Thayan, Ravindran; William, Timothy; Wong, Kum Thong; Tambyah, Paul Anantharajah; Yeo, Tsin Wen (Elsevier, 2019)
[No abstract available]